2008
DOI: 10.1196/annals.1448.022
|View full text |Cite
|
Sign up to set email alerts
|

Circulating DNA

Abstract: Circulating DNA is present in the blood of all individuals, but it has been found that cancer patients and patients with a variety of other conditions have increased amounts of these circulating DNA fragments in their blood. Even though more than 30 years of research have been done on this subject, the origin of these nucleic acid molecules is still not clear. We present evidence that does not support the general notion that apoptosis or necrosis is the major source of circulating free DNA. Active release of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(58 citation statements)
references
References 45 publications
1
55
0
2
Order By: Relevance
“…Extracellular DNA (cell free DNA, cfDNA) is a degradation prod uct that appears as the result of necrosis or apoptosis of cells [6,7]; it is also suggested that cfDNA (metabolic DNA) may be released by living cells [8]. cfDNA com position differs from that of genomic DNA: similarly to bacterial DNA, cfDNA is significantly enriched with GC pairs [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular DNA (cell free DNA, cfDNA) is a degradation prod uct that appears as the result of necrosis or apoptosis of cells [6,7]; it is also suggested that cfDNA (metabolic DNA) may be released by living cells [8]. cfDNA com position differs from that of genomic DNA: similarly to bacterial DNA, cfDNA is significantly enriched with GC pairs [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…ecDNA can also enter the blood fl ow as a result of de novo synthesis in cells (metabolic DNA) [6,14]. ecDNA differ from DNA in cell nucleus: it contains single-and double-strand breaks, accumulates CGenriched genome fragments (CG-DNA), and loses ATenriched fragments [1,3].…”
mentioning
confidence: 99%
“…ecDNA circulates in the blood and other biological fl uids of the organism. The properties of ecDNA are modifi ed under pathological conditions [11]. Our previous studies showed that the concentration of ecDNA in the blood increases during cardiovascular diseases.…”
mentioning
confidence: 99%